2015
DOI: 10.1152/ajpgi.00211.2014
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte TLR4 enhances enteric and systemic inflammation driving late murine endotoxic ileus

Abstract: Buchholz BM, Shapiro RA, Vodovotz Y, Billiar TR, Sodhi CP, Hackam DJ, Bauer AJ. Myocyte TLR4 enhances enteric and systemic inflammation driving late murine endotoxic ileus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Data on myocyte TLR4 function in the setting of endotoxic ileus has demonstrated that non-hematopoietic, non-enterocyte intestinal TLR4 signaling can cause both enteric and systemic inflammation. (34) Given these findings, it is essential to understand the primary source of TLR4 signaling in the intestine after SBR. This information will be critical for future targeting of drug therapies to the appropriate TLR4 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Data on myocyte TLR4 function in the setting of endotoxic ileus has demonstrated that non-hematopoietic, non-enterocyte intestinal TLR4 signaling can cause both enteric and systemic inflammation. (34) Given these findings, it is essential to understand the primary source of TLR4 signaling in the intestine after SBR. This information will be critical for future targeting of drug therapies to the appropriate TLR4 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL1 is also important in normal bowel function. Various diseases, such as endotoxemia [171], brain injury [172] and severe injury trauma [173], are associated with an increase in CXCL1 levels in either the blood or the gut. This leads to a decrease in contraction amplitude in the ileum [173], which results in feeding intolerance and ileus.…”
Section: Ileum and Contraction Amplitudementioning
confidence: 99%
“…In a mouse model of sepsis (BALB/c), gene expression profiling showed that the IL-17 pathway was associated with decreased contraction amplitude and frequency (24 and 48 h) and the blockade of IL-17A (IP injection with IL-17A antibody) improved motility in a cecal ligation and puncture model of sepsis [146]. Buchholz et al also found that IL-17 was associated with late rodent ileus (24 h, C57BL/6) [147]. In a traumatic brain injury rat (SD) model, increased IL-17, along with IL-1α and β, was associated with slowed intestinal transit [148].…”
Section: Il-17mentioning
confidence: 99%
“…The role of CXCL1 in the gut has been mostly studied in the context of inflammatory or infectious diseases. However, CXCL1 is upregulated in animal models of ileus and inhibits intestinal contractile activity in mice and rats [24,147,173]. In addition, CXCL1 was significantly higher in trauma patients who developed ileus compared to trauma patients with no slowed motility [24].…”
Section: Other Inflammatory Mmediators and Signaling Pathwaysmentioning
confidence: 99%